2016
DOI: 10.1007/s12272-016-0864-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and treatment effect of evogliptin on hepatic steatosis in high-fat-fed animal models

Abstract: Dipeptidyl peptidase 4 (DPP4) is an adipokine that interrupts insulin signaling. The resulting insulin resistance exacerbates hepatic steatosis. We previously reported that the novel DPP4 inhibitor evogliptin improves insulin resistance. This study aimed to verify the therapeutic potential of evogliptin for fatty liver. Evogliptin treatment was initiated simultaneously with a high-fat diet (HFD) feeding in normal mice and in a post-24 week HFD-fed rats. In a prevention study, insulin sensitivity was preserved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 47 publications
4
22
0
Order By: Relevance
“…Furthermore, studies in primary human adipocytes showed insulin resistance by the administration of recombinant DPP4 [18] and improved insulin sensitivity when DPP4 was downregulated [20] . Moreover, long-term DPP4 inhibition improved insulin sensitivity and reduced liver fat content in animals with diet-induced hepatic steatosis and insulin resistance [16] , [33] . Thus, DPP4 has an autocrine effect on hepatic insulin signaling which might contribute to later accumulation of ectopic fat in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies in primary human adipocytes showed insulin resistance by the administration of recombinant DPP4 [18] and improved insulin sensitivity when DPP4 was downregulated [20] . Moreover, long-term DPP4 inhibition improved insulin sensitivity and reduced liver fat content in animals with diet-induced hepatic steatosis and insulin resistance [16] , [33] . Thus, DPP4 has an autocrine effect on hepatic insulin signaling which might contribute to later accumulation of ectopic fat in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD is a chronic inflammatory disorder associated with increased hepatic expression of DPP-4; therefore, inhibition of DPP-4 could ameliorate NAFLD [ 16 ]. DPP-4 inhibitors have been reported to decrease lipid accumulation in HFD-induced hepatic steatosis [ 10 , 11 , 12 , 13 , 14 , 17 ]. However, few studies have examined the mechanism underlying the beneficial effects of DPP-4 inhibitors on NAFLD [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evogliptin (Evo), a novel DPP-4 inhibitor, was recently approved for type 2 diabetes by the South Korean Ministry of Food and Drug Safety. It has been found to prevent hepatic steatosis in animal models by suppression of de novo lipogenesis [ 14 ]. However, the precise underlying mechanisms are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…142 They primarily lower the postprandial glucose level, as they inhibit the plasma degrading enzyme DPP-IV, leading to higher plasma GLP-1 levels. 98 There is a good rationale for their use to treat NAFLD as many studies in vitro 143 and in animal models of NAFLD/NASH [144][145][146][147][148][149][150][151][152][153][154] have reported marked beneficial effects.…”
Section: Lactate Amino Acidsmentioning
confidence: 99%